LESSON STUDY SEBUAH SOLUSI PEMBELAJARAN TUNTAS: PENINGKATAN KEMAMPUAN PEDAGOGIK DAN PROFESIONALISME GURU DI SD NEGERI HOLTEKAMP DISTRIK MUARA TAMI KOTA JAYAPURA - Sudaryana Sudaryana; Aisyah Ali (JURNAL PENGABDIAN PAPUA, 2019)
One of the vital compenents in educational system is the teaching and learning activities which is  sometimes the so-called also as instructional activities or education interaction activities. Competence Based Curriculum requires the accurence of mastery learning. Therefore,  to each student has right to attain the mastery in the learning. To reach the mastery learning, a teacher is demanded to be competent in pedagogy and professional. In fulfiling these two competencies, it is considered important towards the professional development via the lesson plan. The research question which emerges on this activity namely: “Can Lesson Study improve the teachers professional and pedagogy competencies to achieve the students mastery learning in SD Negeri Holtekamp District Muara Tami Kota Jayapura?”. This activity aims at improving the teachers’ professional and pedagogy competencies by applying the lesson study to reach the students minimal criteria of mastery of SD Negeri Holtekamp Distrik Muara Tami Kota Jayapura, in the year of 2018. The target of this activity is the head master and teachers in SD Negeri Holtekamp Distrik Muara Tami Kota Jayapura in 2018. This community service carried out using cooperative approach (cooperative learning method), and the interactive colaboration between the facilitator and the participants throughout the study of comprehensive learning. The result of this activity gives the comrehension amid the lesson study as one of the efforts for reaching the students mastery learning. The expectation of this activity should be more developed in which the possible establishment of academic atmosphere condusively for the shake of creating the mutual learning. Thereby, this lesson study potentially hoped to build more and more learning community. For the future, the following teachers personal competency and social competency must have formed fairly.Keywords: papers, teacher professional development, SMPN Sentani